Muslim Scholastic Theology and Social Reform: Shaykh Mohammad Ghazālī’s Perspective - Bensaid, Benaouda; Grine, Fadila (Praeger Publications, 2012)
Social reform does not emerge in vacuum. It requires a comprehensive worldview (Weltanschauung) that answers the arising epistemological, theological and ethical issues. In the Muslim societies, contemporary Muslim thinkers have sought to illustrate the critical role of Muslim theology in shaping the Muslim thought while underscoring not only the socio-historical development of theology, but also the urgent need to formulate new approaches and instruction methods towards a Muslim theology (kalÉm) suited for a positive societal development. This study seeks to analyze the perspective of one prominent Azharite Muslim scholar, Shaykh Mohammad GhazÉlÊ (d.1996), concerning the Muslim theology and social reform and his views on the problems impeding prospect development of a new method of kalÉm. It explores GhÉzÉlÊ’s views with regards to the development of Muslim theology and spirituality, the interface between Muslim beliefs and social reform, the method of the Quran in raising beliefs, and the need for shaping an effective style for instructing Muslim beliefs. The paper concludes that GhÉzÉlÊ’s perspective provides a critical yet constructive insight on the role of Muslim theology for social change in the contemporary Muslim societies.